REHABILITATION IN PALLIATIVE CARE - Minosso,Jéssica Sponton Moura (2016)
ABSTRACT: The objective of this study was to describe the activities and effects of functional rehabilitation in patients receiving palliative care. It is an integrative review, in which LILACS, BDENF, Coleciona SUS (Brazil) and PUBMED were used, 20 articles were selected, subsequently characterized as having designs of medium and low impact, more than half ranked with evidence levels II, III and IV and with samples not always consistent with the research designs. However, the results revealed the potential of rehabilitation to improve the functional status, quality of life and symptoms like pain and anxiety in this population, through interventions that are many times undervalued in palliative care. The conclusion is that rehabilitation is a feasible strategy to combat functional decline and improve the quality of life of patients in palliative care.